2008
DOI: 10.1371/journal.pntd.0000321
|View full text |Cite|
|
Sign up to set email alerts
|

“It Is Me Who Endures but My Family That Suffers”: Social Isolation as a Consequence of the Household Cost Burden of Buruli Ulcer Free of Charge Hospital Treatment

Abstract: Despite free of charge biomedical treatment, the cost burden of Buruli ulcer disease (Bu) hospitalisation in Central Cameroon accounts for 25% of households' yearly earnings, surpassing the threshold of 10%, which is generally considered catastrophic for the household economy, and calling into question the sustainability of current Bu programmes. The high non-medical costs and productivity loss for Bu patients and their households make household involvement in the healing process unsustainable. 63% of househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 9 publications
7
91
1
2
Order By: Relevance
“…Findings confirmed what has been reported by others that BU patients, especially those with severe ulcerated wounds suffer some degree of stigmatization in their communities (Stienstra et al, 2002;Adamba & Owusu, 2011;Peeters et al, 2008;Debacker et al, 2004;Aujoulat et al, 2003;Bigelow et al, 2002). In our study, about 65% of the respondents alluded to the fact that they were teased or laughed at by some community members.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Findings confirmed what has been reported by others that BU patients, especially those with severe ulcerated wounds suffer some degree of stigmatization in their communities (Stienstra et al, 2002;Adamba & Owusu, 2011;Peeters et al, 2008;Debacker et al, 2004;Aujoulat et al, 2003;Bigelow et al, 2002). In our study, about 65% of the respondents alluded to the fact that they were teased or laughed at by some community members.…”
Section: Discussionsupporting
confidence: 88%
“…Most socio-cultural and economic studies on BU reported on local perceptions (beliefs, knowledge and attitudes), and social and economic burdens of the disease to patients and their families (Ahorlu et al, 2013;Stienstra et al, 2002;Adamba & Owusu, 2011;Peeters et al, 2008;Renzaho et al, 2007;Debacker et al, 2004;Aujoulat et al, 2003;Bigelow et al, 2002;Asiedu & Atuaful, 1998). This paper on the other hand focused on identifying social and economic factors that are considered when the affected and infected are making health seeking decisions on where and when to seek for health.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that at these low incidence levels, the inequalities created in the population as a result of highly debilitating diseases can be significant. A sustained long-term annual incidence of 5 to 20 cases 1000py 21 can leave a significant proportion of the population with permanent disabilities. In the context of low-resource settings, where no subsidies exist for disabled individuals and most economic activities rely heavily on physical labour, such a disability burden results in a major economic burden.…”
Section: Discussionmentioning
confidence: 99%
“…Direct non-medical costs associated with treatment (x i ) such as transportation to the health centre and feeding costs are deducted from income for individuals undergoing treatment [21,22,34]. Importantly, when the individuals in the model are renewed (one individual dies and is replaced by a new born), the offspring 'inherits' the physical capital of the individual they replace (their 'parent').…”
Section: (B) Economic Growth Modelmentioning
confidence: 99%
“…Moreover, it has been determined for Central Cameroon that despite free-of-charge medical treatment, the cost burden of BUD accounts for 25% of households' yearly earnings, surpassing the threshold of 10%, which is generally considered catastrophic for the household economy, and calling into question the sustainability of current BUD programs [21].…”
Section: Treatmentmentioning
confidence: 99%